2011
DOI: 10.1179/107902611x12972448729648
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of TIMP-2 and collagen types I and IV in experimental spinal cord ischemia–reperfusion injury in rats

Abstract: Background: Thoracic and thoracoabdominal aortic intervention carries a significant risk of spinal cord ischemia. The pathophysiologic mechanisms that cause hypoxic/ischemic injury to the spinal cord have not been totally explained. In normal spinal cord, neurons and glial cells do not express type IV collagen. Type IV collagen produced by reactive astrocytes is reported to participate in glial scar formation. Tissue inhibitors of metalloproteinases (TIMPs) are endogenous inhibitors that regulate the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It has been suggested that acute and chronic spinal cord ischemic injury may in fact induce the passage of blood borne or neurotrophic substances (specifically TNF- α ) through the BBB past its saturation point [14, 1618]. It appears that decoupling of astrocyte foot processes from endothelial cell surfaces inhibits tight junction function in the BBB [15, 19, 20]. Transport systems and ionic buffering would then be disrupted allowing worsened reperfusion injury upon decompression of a previously ischemic spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that acute and chronic spinal cord ischemic injury may in fact induce the passage of blood borne or neurotrophic substances (specifically TNF- α ) through the BBB past its saturation point [14, 1618]. It appears that decoupling of astrocyte foot processes from endothelial cell surfaces inhibits tight junction function in the BBB [15, 19, 20]. Transport systems and ionic buffering would then be disrupted allowing worsened reperfusion injury upon decompression of a previously ischemic spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological samples were fixed, embedded in paraffin, and cut into 5-µm slices. Following deparaffinizing and rehydrating, antigen retrieval was performed according to standard protocols (17). Following treatment with 3% H 2 O 2 in methanol and normal non-immune goat serum (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) for 20 min at room temperature, the sections were incubated overnight at 4˚C with primary antibodies against RAGE (1:1,000; catalog no.…”
Section: Assessment Of Locomotor Function Recovery Of Locomotor Funcmentioning
confidence: 99%
“…MMP-14 was the first MMP discovered possessing a transmembrane domain cloned from lung tumor cells conferring their invasiveness and metastasis (51). A study focusing on ischemia-reperfusion in the spinal cord injury of rats reported that TIMP-2 binding to MMP-2 activates MMP-14 (52). Furthermore, MMP-14 has been found to be involved in neuroinflammation (53).…”
Section: Types Of Mmps and Their Involvement In Diseasesmentioning
confidence: 99%